Short-term prolactin administration causes expressible galactorrhea but does not affect bone turnover: pilot data for a new lactation agent - Page-Wilson, Gabrielle (BioMed Central, 2007)
BACKGROUND: Medications used to augment lactation increase prolactin secretion but can have intolerable side effects. We examined the biological activity of recombinant human prolactin (r-hPRL) as preliminary data for its use to augment lactation. METHODS: Healthy, non-postpartum women (n = 21) with regular menstrual cycles underwent a seven day randomized, double-blind, placebo-controlled trial of r-hPRL. Expressible galactorrhea, markers of bone turnover, calcium homeostasis and gonadal function were measured and side effects recorded. RESULTS: Prolactin levels increased during r-hPRL administration (20.0 ± 2.8 to 231.7 ± 48.9 μg/L at 6 hours; p < 0.05). Five of nine participants who received r-hPRL developed expressible galactorrhea (p < 0.001). Urinary deoxypyridinoline decreased and bone specific alkaline phosphatase increased in r-hPRL and placebo groups. Menstrual cycle lengths were not altered and side effects were similar between r-hPRL and placebo groups. CONCLUSION: In summary, r-hPRL can cause expressible galactorrhea. Seven days of r-hPRL administration does not adversely affect bone turnover or menstrual cyclicity. Thus, r-hPRL may be a viable option for short-term lactation augmentation. TRIAL REGISTRATION: Clinical Trials.gov NCT00438490